2014
DOI: 10.1111/scs.12168
|View full text |Cite
|
Sign up to set email alerts
|

A room of one′s own – Being cared for in a hospital with a single‐bed room design

Abstract: Patients experienced that a single-bed room allowed them to focus on their recovery, have visitors without disturbing others and create a feeling of homeliness. However, mobilisation is not a natural part of the recovery process when patients have all they need in their rooms. The patients' need for social interaction and confirmation was not satisfied without effort and planning on the part of staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 24 publications
3
73
1
1
Order By: Relevance
“…There is an ongoing debate regarding whether hospital units should be designed exclusively with single rooms or multi-bed rooms, with a general trend towards the provision of single rooms in new health care buildings [30, 32, 33]. The most important argument for a single-room design is the reduction of airborne- and contact-transmitted infections [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ongoing debate regarding whether hospital units should be designed exclusively with single rooms or multi-bed rooms, with a general trend towards the provision of single rooms in new health care buildings [30, 32, 33]. The most important argument for a single-room design is the reduction of airborne- and contact-transmitted infections [12].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies have highlighted the complexity of the issues related to single rooms [30, 32, 38]. While some patients have reported that they preferred single rooms because the rooms allowed them to create a personal and private environment [32], staff have reported disadvantages related to visibility, surveillance, teamwork, monitoring and keeping patients safe [30].…”
Section: Discussionmentioning
confidence: 99%
“…33 Patients who had their own room experienced physical loneliness. 41 Physical loneliness was associated with the alien hospital environment, but also with having to leave home and having to give up one's earlier lifestyle, hobbies, and important relationships and freedom. Loneliness was described as alienation and anxiety.…”
Section: Loneliness In the Environment And Physical Lonelinessmentioning
confidence: 98%
“…Risk of patients isolating in single rooms and not getting out of bed is a step back seen in the context of fast track surgery progress where early mobilization is a main reason for shorter hospital stay. When patients have all they need in their room they are not naturally encouraged to get out of bed [16]. This theory is supported by Williams et al who found that patient in single-rooms were more likely to use the bell more often because they felt isolated and not safe going out of bed alone [21].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that social interaction with other patients was not facilitated without effort and planning from the staff [16]. In single bedrooms the staffs is often the patient's main contact given that most patients stay in their room.…”
Section: Introductionmentioning
confidence: 99%